2017
DOI: 10.12693/aphyspola.132.1102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phase Change Materials on Time Lag, Decrement Factor and Heat-Saving

Abstract: In this study, the effect of phase change materials on the time lag, decrement factor and heat-saving is examined numerically. The calculations are conducted for four different cities located at different climatic zones in Turkey, considering both summer and winter conditions, in order to explore the potential heating and cooling energy savings by employing phase change materials. A solar-air temperature, which is a function of time and solar radiation, was taken into consideration as external boundary conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A recent study in 2017, indicated that the employment of phase change materials in walls of a building has a pronounced effect on the time lag and the decrement factor. It is concluded that a significant amount of heating energy can be saved, and thermal comfort can be considerably enhanced, by incorporating phase change materials into external walls (Bilgin and Arici 2017).…”
Section: Previous Studies On Df Tdr and Tgmentioning
confidence: 99%
“…A recent study in 2017, indicated that the employment of phase change materials in walls of a building has a pronounced effect on the time lag and the decrement factor. It is concluded that a significant amount of heating energy can be saved, and thermal comfort can be considerably enhanced, by incorporating phase change materials into external walls (Bilgin and Arici 2017).…”
Section: Previous Studies On Df Tdr and Tgmentioning
confidence: 99%
“…Thongtha et al [10] reported that the time lag is directly proportional to the wall thickness, while the decrement factor is inversely proportional to the wall thickness. Bilgin and Arici [11] found through a simulation model that for the PCM wall in Ankara, Turkey, TL increased from 5.64 to 16.11h, and DF decreased from 0.144 to 0.034. Kuznik et al [12] concluded that the PCM layer increases the TL by 1.66 hours.…”
Section: Introductionmentioning
confidence: 99%